Latinx Mental Health Scholars' Experiences with Cultural Adaptation and Implementation of Systemic Family Interventions. Issue 2 (4th March 2019) - Cooper, Daniel K.; Wieling, Elizabeth; Domenech Rodríguez, Melanie M.; Garcia‐Huidobro, Diego; Baumann, Ana; Mejia, Anilena; Le, Huynh‐Nhu; Cardemil, Esteban V.; Acevedo‐Polakovich, Ignacio D.
Abstract : An increasing number of culturally adapted family‐level interventions address mental health disparities with marginalized populations in the United States. However, with these developments many barriers have arisen, such as challenges with degree of cultural fit, engagement, and sustainability. We conducted 12 elite phenomenological interviews with mental health scholars involved in prevention and intervention family research with various Latinx communities within and outside of the United States. These scholars discussed their experiences of overcoming barriers in their research. We used thematic analysis to code and analyze participant responses, and our findings support the gaps in previous literature and highlight potential pathways to overcoming barriers in cultural adaptation research. Themes included the need for: (a) better understanding of the intersection between culture and context; (b) community‐centered approaches to addressing implementation challenges; and (c) structural changes within institutional, governmental, and political levels. We discuss implications for researchers and practitioners working with Latinx families. Abstract : Un número cada vez mayor de intervenciones adaptadas culturalmente a nivel familiar abordan las desigualdades en la salud mental con poblaciones marginadas en los Estados Unidos. Sin embargo, con estos avances han surgido muchos obstáculos, como las dificultades con el grado de integración cultural, la participación y la sostenibilidad. Realizamos veinte entrevistas fenomenológicas selectas con investigadores de la salud mental dedicados a la investigación familiar en materia de prevención e intervenciones con varias comunidades latinas dentro y fuera de los Estados Unidos. Estos investigadores comentaron sus experiencias de superación de los obstáculos en su investigación. Utilizamos el análisis temático para decodificar y analizar las respuestas de los participantes; nuestros resultados respaldan la falta de datos en publicaciones previas y destacan las posibles vías para superar los obstáculos en la investigación sobre la adaptación cultural. Los temas incluyeron la nacesidad de: (a) una mejor comprensión del enlace entre la cultura y el contexto; (b) enfoques centrados en la comunidad para abordar las dificultades de implementación; y (c) cambios estructurales dentro de los niveles institucionales, gubernamentales y políticos. Debatimos las implicancias para los investigadores y los profesionales que trabajan con familias latinas. Abstract : 针对特定文化族群的家庭层面干预来解决处于美国社会边缘的人群心理健康差距问题的做法越来越多, 但是在其发展过程中也会遇到一些障碍, 比如文化适应程度方面的困难, 如何让病人配合和治疗措施持续性的问题等等。我们对12名顶级的心理健康学者进行了现象学的访谈, 这些学者均参与过针对很多在美国境内和境外的拉丁美洲社群家庭进行预防和干预的家庭研究。他们都谈到了他们在研究过程中克服障碍的经历。我们使用主题分析法来解码和分析参与者的访谈内容, 我们的结果显示在以前的文献中此类研究选题确实存在空白, 并指出了克服这些文化调适研究中的障碍的可能路径。主题包括有必要:(a)更好地理解文化和具体生活环境共同的相互作用;(b)以社群为中心的方法来讨论实施过程中的困难;(c)在体制、政府和政治层面进行结构化变革。我们给出了研究者和从业者在跟拉丁美洲家庭打交道时的一些建议。